2009
DOI: 10.1161/strokeaha.108.528588
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Is Induced in the Ischemic Cerebral Cortex and Exerts Neuroprotection Through NF-κB/c-Rel–Dependent Transcription

Abstract: Background and Purpose-Leptin is an adipose hormone endowed with angiopoietic, neurotrophic, and neuroprotective properties. We tested the hypothesis that leptin might act as an endogenous mediator of recovery after ischemic stroke and investigated whether nuclear transcription factors B activation is involved in leptin-mediated neuroprotection. Methods-The antiapoptotic effects of leptin were evaluated in cultured mouse cortical neurons from wild-type or NF-B/c-Rel Ϫ/Ϫ mice exposed to oxygen-glucose deprivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 33 publications
6
78
0
1
Order By: Relevance
“…4, I and J). Leptin Causes Hypothalamic NF-B Activation-Previous studies have shown that leptin, an important anorexigenic hormone, activates NF-B in cortical neurons, microglia, and astrocytes from the brain (32)(33)(34). Therefore, we investigated whether leptin also causes hypothalamic NF-B activation.…”
Section: Inhibition Of Nf-b In Pomc Neuronsmentioning
confidence: 98%
“…4, I and J). Leptin Causes Hypothalamic NF-B Activation-Previous studies have shown that leptin, an important anorexigenic hormone, activates NF-B in cortical neurons, microglia, and astrocytes from the brain (32)(33)(34). Therefore, we investigated whether leptin also causes hypothalamic NF-B activation.…”
Section: Inhibition Of Nf-b In Pomc Neuronsmentioning
confidence: 98%
“…Further investigations confirmed that p50 and RelA subunit activation contributes to the apoptotic program in cells exposed to the β-amyloid peptide (Akama et al, 1998;Pizzi et al, 2005b;Valerio et al, 2006). In addition, the c-Rel-containing dimers p50/c-Rel and RelA/c-Rel are involved in neuroprotective effects elicited by S100B (Kögel et al, 2004), agonists at the metabotropic glutamate type 5 (mGlu5) receptors (Pizzi et al, 2005b;Sarnico et al, 2008b) or leptin (Valerio et al, 2009). Neuroprotection elicited by c-Rel against β-amyloid toxicity was associated with the expression of the antiapoptotic proteins B-cell lymphomaextra large (Bcl-x L ) and manganese superoxide dismutase (MnSOD) (Pizzi et al, 2005b) (Fig.…”
Section: Nf-κb In Neuron Survivalmentioning
confidence: 82%
“…Furthermore, the adipocyte-derived hormone leptin, by activating c-Relcontaining dimers c-Rel/p50 and c-Rel/RelA, significantly increased Bcl-x L expression and reduced the infarct volume in mice exposed to permanent MCAO. As a confirmation of the pivotal role of c-Rel in limiting apoptosis, the protective effect of leptin in brain ischemia was suppressed in c-Rel deficient mice (Valerio et al, 2009). …”
Section: Nf-κb and Strokementioning
confidence: 88%
“…2 Accordingly, leptin treatment did not affect cerebral blood flow as assessed by laser Doppler analysis in our study. 3 As Dr Tsuda correctly mentioned, evidences indicate that NO has a role in neuroprotection. Compelling data from animal models demonstrate that NO generated by endothelial NO synthase (eNOS) plays a protective role against ischemic stroke.…”
Section: Responsementioning
confidence: 99%
“…7,8 Improved bioenergetics due to mitochondrial biogenesis augment tolerance to ischemic injury. 11 Thus, besides the NFB/c-Rel-mediated inhibition of neuronal apoptosis, 3 eNOS/PGC-1␣ mediated phenomena, including mitochondrial biogenesis, might take part to the protective effects of leptin against cerebral ischemia. The latter point is currently under investigation in our laboratories.…”
Section: Responsementioning
confidence: 99%